Support for resettling refugees : the role of fixed versus growth mind-sets - Madan, Shilpa (2020)
In six studies (N = 2,340), we identified one source of people’s differential support for resettling refugees in their country—their beliefs about whether the kind of person someone is can be changed (i.e., a growth mind-set) or is fixed (i.e., a fixed mind-set). U.S. and UK citizens who believed that the kind of person someone is can be changed were more likely to support resettling refugees in their country (Studies 1 and 2). Study 3 identified a causal relationship between the type of mind-set people hold and their support for resettling refugees. Importantly, people with a growth mind-set were more likely to believe that refugees can assimilate in the host society but not that they should assimilate, and the belief that refugees can assimilate mediated the relationship between people’s mind-sets and their support for resettling refugees (Studies 4–6). The findings identify an important antecedent of people’s support for resettling refugees and provide novel insights into the science of mind-sets.